Clinical, Paraclinical, and Evolutionary Profiles of Kidney Failure in Gold Miners Hospitalized in a Nephrological Service in a Sub-Saharan African Country - Gérard Coulibaly; Gaoussou Sanou; Moumouni Sanon; Aïda H. Y. Lengani; Juste Y. Bonzi; Aoua Semde (International Journal of Nephrology)
Introduction. The purpose of this preliminary study is to describe the clinical, paraclinical, and evolutionary profiles of gold miner patients with kidney failure hospitalized in the nephrology and haemodialysis service in the Yalgado Ouédraogo University Hospital of Ouagadougou (CHU-YO). Patients and Methods. This was a longitudinal and descriptive study with a retrospective collection of data for the period from February 1, 2013, to March 31, 2018. Included were all gold miner patients who stayed and worked at an artisanal gold mining site for at least three months and who were diagnosed with acute or chronic kidney failure during hospitalization in the nephrology service. We collected sociodemographic, clinical, and paraclinical variables at admission and then three months later. Results. We included 50 patients; all were male and the average age was 29.4 ± 7.7 years. All patients were exposed to mercury and/or cyanide for an average of 4.5 ± 2.8 years. The average consultation/referral time for patients at the CHU-YO was 25.4 ± 14.9 days. The average of creatininemia was 2338.0 ± 791.4 μmol/L. Kidney failure was acute in five cases (10%) and chronic in the remaining 45 cases or 90%. Extrarenal purification was indicated in 43 cases (86%). It was not performed in nine of the 43 cases due to lack of financial resources for patients (six cases) or death prior to the onset of haemodialysis (three cases). Thirty-two of the 50 patients in the study (64% of cases) died. Conclusion. Chronic kidney failure in gold miners appears to be common and late-managed. A prospective study of kidney disease and its causes at gold mining sites and surrounding areas will assess the extent of the problem in the country and better clarify the prevention of these diseases in our country.